Association of Coffee and Caffeine Intake With Irritable Bowel Syndrome in Adults - Koochakpoor, Glareh; Salari-Moghaddam, Asma; Keshteli, Ammar Hassanzadeh; Esmaillzadeh, Ahmad; Adibi, Peyman (Frontiers in Nutrition, 2021)
The aim of this study was to investigate the association between coffee and caffeine intake and odds of IBS and its severity in adult population. In this cross-sectional study, dietary intakes of 3,362 Iranian adults were examined using a validated dish-based 106-item Semi-quantitative Food Frequency Questionnaire (DS-FFQ). Coffee and caffeine intake was assessed using the DS-FFQ. IBS was assessed using a modified Persian version of Rome III questionnaire. After adjustment for potential confounders, we found that individuals who were taking coffee weekly or more had greater odds of IBS (OR:1.44; 95% CI: 1.02-2.04) than those who never drinking coffee. In addition, participants in the top tertile of caffeine intake (≥106.5 mg/d) had 47% greater odds of IBS compared to those in the bottom tertile (<69.4 mg/d) (OR: 1.47; 95% CI: 1.14-1.87). By gender, a significant association was observed between caffeine intake and odds of IBS among women (OR for those in the highest tertile vs. lowest tertile: 1.48; 95% CI: 1.10-2.00), but not in men (OR: 1.47; 95% CI: 0.94-2.30). In addition, a significant positive association was seen between caffeine intake and odds of IBS among subjects with BMI ≥ 25 kg/m2 (OR for those in the highest tertile vs. lowest tertile: 1.72; 95% CI: 1.20-2.48). There was a significant association between caffeine intake and IBS severity among subjects with BMI ≥ 25 kg/m2 (OR: 1.04; 95% CI: 1.01-2.62). In conclusion, coffee and caffeine consumption was associated with increased odds of IBS in the whole study population. The association between caffeine and odds of IBS was also significantly positive among women and overweight or obese subjects (BMI ≥ 25 kg/m2). In addition, we found a significant relationship between caffeine intake and severity of IBS symptoms among overweight or obese subjects (BMI ≥ 25 kg/m2).